The influence of personnel management policy on motivation of employees in the service industry - Nurmukhan, G.; Kussaiyn, A.; Rakhimgaziyeva, Y.; Shekimov, T. (International School of Economics KAZGUU, Nur-Sultan, 2022)
This work is devoted to the study of staff motivation and the development of recommendations for solving the problem of low motivation of staff at hotel enterprises. A literature review was done on the issue of the connection of HR policies and staff motivation. The purpose of this research was to identify the influence of properly developed and implemented HR policies on staff motivation. After the literature review the methodology design was done. To identify the results of the study was conducted quantitative and qualitative research methods. The study revealed what and who can motivate employees and HR managers of St.Regis and Jumbaktas hotels, and also considered the problem of staff turnover, the correct personnel policy and a comparison of the internal structure of hotels. This research will help Jumbaktas Hotel to, increase employee motivation and develop a new HR policy structure. Consequently, a more detailed study of the literature was made, as it was found out that this topic was insufficiently studied in Kazakhstan. It was decided to conduct a survey dividing the participants into managerial and non-managerial positions of two hotels. The survey included information about employee motivation and the level of formalization and impact of HR policy. Interviews were also conducted with the management in order to assess how HR policies are developed and used. According to the results of the study, a link was revealed between the presence of good work of HR politicians and employees. Keywords: hotel, motivation, effectiveness, employee, HR policy, problem, wages, Jumbaktas, St.Regis,
Keywords: hotel, motivation, effectiveness, employee, HR policy, problem, wages, Jumbaktas, St.Regis, managerial, non – managerial. problem tree